Viral diseases of cardamom (Elettaria cardamomum Maton) and their management - VENUGOPAL, M N (Journal of Spices and Aromatic Crops, 1995)
Small cardamom (Elettaria cardamomum Maton) is affected by many diseases which have been identified as a major production constraint. Among the viral diseases ’katte’ or mosaic is the major viral disease causing severe yield losses to an extent of 68 per cent. In addition, Nilgiri necrosis, infectious variegation virus and ’kokke kandu’ diseases are gaining importance in recent years. The present paper reviews the information available on distribution of viral diseases, symptomatology, crop loss, transmission, etiology, host range and disease management. The future plan of work on aspects such as breeding for disease resistance through genetic engineering, virus characterization and early detection methods are indicated.